2019
DOI: 10.1590/18094449201900550016
|View full text |Cite
|
Sign up to set email alerts
|

"Fazer emergir o masculino": noções de "terapia" e patologização na hormonização de homens trans

Abstract: Resumo Descreve-se as noções de "terapia" hormonal em cenários medicalizantes nos quais homens transexuais se movem na constituição de transições de gênero. Em meio aos acessos e práticas à (auto)administração de ésteres de testosterona (cipionato e/ou propionato), esses sujeitos acionam a ideia de "terapia" - seja para se afastar ou para reiterá-la -, levando-nos a uma reflexão sobre a atual classificação da transexualidade como doença mental. Realizou-se pesquisa etnográfica em grupos de ativismo trans no Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 11 publications
(6 reference statements)
0
7
0
11
Order By: Relevance
“…With contexts demarcated by religion, whose logic of sinfulness, the idea of a “dirty, unworthy, sinful and erroneous body”, can intensify the transphobia perpetrated by family members against the “gender-divergent person”. This reality can revert to triggering negative feelings/emotions, reflecting the indignation and impact suffered by those who should be the primary source of support/ support, safety/protection and expression of affection/love ( 23 , 24 ) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…With contexts demarcated by religion, whose logic of sinfulness, the idea of a “dirty, unworthy, sinful and erroneous body”, can intensify the transphobia perpetrated by family members against the “gender-divergent person”. This reality can revert to triggering negative feelings/emotions, reflecting the indignation and impact suffered by those who should be the primary source of support/ support, safety/protection and expression of affection/love ( 23 , 24 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Faced with these circumstances, trans and transmasculine men can become discreet, almost invisible to people’s eyes, due to the fear of expressing their identities socially and establishing their body readings in front of others, through the fear of delegitimization, embarrassment, humiliation and other forms of violence and social oppression ( 23 , 24 ) . Under this issue, our findings in this present study revealed that this fact may be related to the way trans men and transmasculine people deal with self-image and body image, as in the case of the breasts, an organ that compromises the body archetype “passing” and configuration and the male figure aesthetics ( 23 ) in social imaginary. In view of this, it is salutary to create specific lines of care for specialized, comprehensive and equitable health care in the health network available to the trans population, in addition to qualification of nursing teams in health care promotion with a view to valuing trans identities, self-image/perception and self-concept.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A Organização Mundial da Saúde (OMS), em 2018, através da nova Classificação Estatística Internacional de Doenças e Problemas Relacionados à Saúde (CID-11), removeu o chamado transtorno de identidade sexual constante no CID-10 como doença mental, colocando a situação de incongruência de gênero como parte do item Condições Relacionadas à Saúde Sexual para identificar a pessoa transexual 4 No Brasil, a hormonização é disponibilizada pelo Ministério da Saúde, sendo denominada de Processo Transexualizador. O usuário que procura no sistema de saúde o amparo para sua condição de sofrimento decorrente da incompatibilidade entre o sexo biológico e o sentimento de pertencimento a um gênero de identificação será acolhido e submetido à avaliação inicial, feita por um psicólogo e outro profissional da equipe multiprofissional, em ambulatório ou hospital credenciado, com a finalidade de confirmar a Disforia de Gênero 6 . A prevalência de tal condição é bastante variável, podendo ser de 6 à 521 por 100.000 habitantes, em se tratando de mulheres trans e 2,5 a 256 por 100.000 habitantes para homens trans 7 .…”
Section: Introductionunclassified